1998
DOI: 10.4315/0362-028x-61.10.1293
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Environmental Stress on the Ability of Listeria monocytogenes Scott A To Attach to Food Contact Surfaces

Abstract: Attachment of Listeria monocytogenes Scott A to Buna-N rubber and stainless steel under different temperature and pH conditions at the time of cell growth or at the time of attachment was investigated. All experiments were conducted using sterile phosphate buffer to avoid cell growth during exposure to the test surfaces. Numbers of attached cells increased with increasing attachment temperature (10 to 45 degrees C) and exposure time for both test surfaces. Maximum levels of attached cells were obtained when ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
46
0
4

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 63 publications
2
46
0
4
Order By: Relevance
“…To understand how the bacterium establishes a niche and persists on foodprocessing equipment, the attachment of L. monocytogenes to abiotic surfaces, such as stainless steel and rubber, has been studied (32,52,53,57). We have developed a model system with cut radish tissue to study the molecular mechanisms involved in L. monocytogenes attachment to plant surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…To understand how the bacterium establishes a niche and persists on foodprocessing equipment, the attachment of L. monocytogenes to abiotic surfaces, such as stainless steel and rubber, has been studied (32,52,53,57). We have developed a model system with cut radish tissue to study the molecular mechanisms involved in L. monocytogenes attachment to plant surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…If cell numbers are high, fluorescence microscopy is useful, although a detailed quantification is difficult when bacteria are arranged in clusters or layers. Some authors detach bacteria from the surface by ultrasound, by mixing, or by swabbing (38) and quantify these by standard plate counts thereafter. Ultrasonic removal of cells has been used by several authors (24,34), and we found that this procedure for quantification was in excellent agreement with counts obtained using Malthus detection times converted via a standard curve.…”
Section: Discussionmentioning
confidence: 99%
“…Bio®lm formation is a complex process and many factors in¯uence bacterial attachment to surfaces, such as: surface conditioning and type of growth medium (Shapiro 1991;Helke et al 1993;Briandet et al 1999), growth temperature (Smoot and Pierson 1998), growth pH (Lindsay et al 2000a), electrostatic and physical interactions between bacterial cell surfaces and the substratum (Costerton et al 1987;Van Loosdrecht et al 1990;Flemming et al 1998) and bacterial cell-to-cell communication and signalling (Stewart et al 1996;Davies et al 1998;Stoodley et al 1999). In addition, the colonization of a surface by one bacterium can reportedly enhance the attachment of others to the same surface (Sasahara and Zottola 1993;Jones and Bradshaw 1997;Mùller et al 1998).…”
Section: Introductionmentioning
confidence: 99%